CONGENITAL ANOMALIES AMONG NEWBORNS - Devassy, Unnimon K.; M., Danasegaran; Sailesh, Kumar Sai; Mishra, Soumya; Reddy, Udaya Kumar; J., Antony N. (BALI MEDICAL JOURNAL, 2015)
Background: The present study was undertaken to assess the incidence of congenital anomalies among newborns. The total anomalies were 280 and the highest incidence has been identified in the year 2011, and the incidences were high in the gastrointestinal system. It also reveals that the incidence is higher in low birth weight newborns, and the major incidence has been identified in full term newborns. Results: results of the study can be used to predict future incidence of anomalies and to increase public awareness about congenital anomalies to take preventive measures.